(untitled) (Materiali di Estetica. Terza serie, 2024)
Daniele Goldoni’s essay, Una Crepa. Adesso, is a philosophical reflection on Fulvio Papi’s legacy and the enduring relevance of his thought. Goldoni delves into Papi’s concept of the “crepa” (fissure), which symbolizes the tension between the solidity of established narratives and the uncertain, fragmented perception of reality. The text explores themes of temporality, crisis, and the plurality of lived experiences, critiquing the dominance of global capitalism while advocating for a philosophy grounded in care, human connection, and the acceptance of imperfection. Through references to metaphysics, everyday life, and the urgency of present crises, the essay invites us to inhabit the “crepa” as a space of philosophical and existential possibility. Goldoni closes with a call for a philosophy that listens to the voices of the present and responds with love, gratitude, and action, even amidst a fractured world.